Geochemical characteristics and origin of crude oil from Carboniferous volcanic rocks in the Hongche Fault Zone of the Junggar Basin of China - He, Qingbo; Chen, Shijia; Wang, Jian; Zhao, Liping; Ma, Zhiwei (Frontiers in Earth Science, 2022)
In recent years, the exploration of Carboniferous volcanic reservoirs in the Hongche fault zone in the Junggar Basin of China has made great breakthroughs, showing good prospects for exploration. Volcanic reservoirs in this area have the characteristics of distribution along the fault zone, but the types of crude oil in them are complex and diverse, so that the law of crude oil distribution is still unclear. The organic geochemical characteristics of Permian Fengcheng Formation (P1f), Permian Lower Wuerhe Formation (P2w), Permian Jiamuhe Formation (P1j) source rocks and Carboniferous crude oils are studied. After analysis the oil-source correlation, the accumulation model for volcanic reservoirs in the study area is established. The results show that the physical properties, composition, Pr/nC17 and Ph/nC18 of crude oil in this area have a wide distribution range. Some crude oils have the serious lack of n-alkanes, but pentadiene, β-carotane, terpane series and sterane series are preserved intact, indicating that this part of crude oil has suffered less than 5-7 biodegradation (PM<5-7). Carboniferous crude oil in the study area has higher abundance of β-carotane, higher abundance of gammacerane, lower abundance of Pr/Ph ratio, and has the distribution characteristics of the advantages of C23 tricyclic terpenes and C29 regular steranes. It also proves that Carboniferous crude oil in this area is mainly derived from the Fengcheng Formation (P1f) source rock in the mature stage of the Late Triassic. In addition, migration and accumulation of oil and gas and the degree of biodegradation of crude oils are closely related to fault activities. The strong tectonic action in the later period caused serious oil and gas loss in some areas and suffered biodegradation to form high-density heavy oil.